Kardiochirurgia DorosłychThe surgical ablation of substrate of atrial fibrillation in the surgical treatment of arrhythmia - Sarnowski, Wojciech; Perek, Bartłomiej; Stachowiak, Wojciech; Buczkowski, Piotr; Urbanowicz, Tomasz; Misterski, Marcin; Puślecki, Mateusz; Paluszkiewicz, Lech; Katarzyński, Sławomir; Tomczyk, Jadwiga; Ligowski, Marcin; Jemielity, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: Some patients after valve replacement do not improve postoperatively as far as functional status is concerned, because of coexistent atrial fibrillation (AF). Aim: The aim of this study was to evaluate the efficacy of irrigated radiofrequency endocardial ablation (IRF) in patients with organic valve diseases treated surgically. Material and methods: Our study involved 79 pts. (24 M, 55 F) with the mean age of 60.7±7.9 years. The primary indication for surgery was: mitral valve disease in 42 patients, aortic valve disease in 4 pts, combined mitral and aortic valve disease in 9 pts, combined mitral and tricuspid valve disease in 11, three valves in 2 pts. We divided the patients into two groups according to the type of atrial fibrillation: group I (n=33) with permanent AF, and group II with paroxysmal AF (n= 35), due to monopolar IRF ablation. All the patients were operated on with cardiopulmonary bypass. After opening the left atrium, endocardial radiofrequency ablation was performed according to modified Maze III technique. Results: There was one early postoperative death (5th day) due to heart failure. After the operation the rate of sinus rhythm (SR) in group I was 66%, and in group II 74% SR. After the follow-up of 7 days the rate of sinus rhythm was 57% and 82% respectively in group I and group II. The follow-up of one month showed a rate of sinus rhythm of 57% in group I and 82% in group II, and six months after the surgery the rate of SR decreased to the value of 43% in group I and to 76% in group II. Conclusion: Surgical endocardial radiofrequency ablation treatment is a proper method of treatment for patients with valvular heart disease coexisting with AF.